Investigating NFE2L1 activators for targeted protein aggregate clearance: a follow-up study - Smahelova, Zuzana; Svobodova, Lucie; Sedlacek, Jindrich; Adamek, Michael; Pimkova Polidarova, Marketa; Majer, Pavel; Machara, Ales; Saskova, Klara Grantz (RSC medicinal chemistry, 2025)
Disruption of protein homeostasis (proteostasis), whether by acute proteotoxic stress or chronic expression of mutant proteins, can lead to the accumulation of toxic protein aggregates. Such aggregation is a hallmark of numerous diseases and is often associated with impaired protein clearance mechanisms. The transcription factor nuclear factor erythroid 2-related factor 1 (encoded by NFE2L1, also known as Nrf1) plays a central role in restoring proteostasis by increasing proteasome synthesis. Therefore, pharmacological activation of NFE2L1 under non-stress conditions represents a promising therapeutic strategy for neurodegenerative and other proteostasis-related diseases. In our previous study, we identified bis(phenylmethylene)cycloalkanone derivatives as NFE2L1 activators capable of inducing proteasome subunit expression, increasing heat shock protein levels, and stimulating autophagy. Building upon these findings, we have now developed a new library of structurally related compounds to identify novel more potent NFE2L1 activators. By systematically examining how specific chemical substitutions affect NFE2L1 activation, this work advances our understanding of the structure-activity relationships within this pathway.